Comparison of the Electrical Properties of PERC Approach Applied to Monocrystalline and Multicrystalline Silicon Solar Cells. (4th October 2016) - Wang, Enyu; Wang, He; Yang, Hong
Abstract : At present, the improvement in performance and the reduction of cost for crystalline silicon solar cells are a key for photovoltaic industry. Passivated emitter and rear cells are the most promising technology for next-generation commercial solar cells. The efficiency gains of passivated emitter and rear cells obtained on monocrystalline silicon wafer and multicrystalline silicon wafer are different. People are puzzled as to how to develop next-generation industrial cells. In this paper, both monocrystalline and multicrystalline silicon solar cells for commercial applications with passivated emitter and rear cells structure were fabricated by using cost-effective process. It was found that passivated emitter and rear cells are more effective for monocrystalline silicon solar cells than for multicrystalline silicon solar cells. This study gives some hints about the industrial-scale mass production of passivated emitter and rear cells process.